The ethics of care as a form of feminist political organization in Costa Rica - Guzmán Sierra, Silvia Elena (2022)
This article is the result of the systematization of the experience lived with 8 women from 4 feminist collectives, who, based on their situated knowledge, allow us to venture to reflect on an epistemology of care, and the political act of transferring care from the private sphere to the public space, which we understand as ethics of care. From their organizational praxis, three fundamental axes are drawn for these ethics, such as the linking organization, collective care and affectivity.